Estrogens occurring in slaughtered female calves - Silva, Carlos Antonio Mondino; Grunert, Eberhard; Pózvári, Marianne (Pesquisa Agropecuaria Brasileira, 2014)
The mice-uterus test, t.l.c. and concomitant macroscopic examination of respective ovaries were used to examine the faeces of 66 slaughtered female calves for the presence of substances having oestrogenic action. Follicles with a diameter of more than 6 mm were only observed in 13 cows, whilst those found in the ovaries of the remainder (53) had follicles between 2 and 3 mm in diameter. An extract of calves faeces administered orally to adolescent female mice resulted in: a) Extracts from those 13 cows with ovaries having follicles with diameters more than 6 mm, no significant difference in uterine weight between test and control mice; b) Extracts from the remaining cows; highly significant (P < 0.001) differences between uterine weight of test and control mice of 47 cases; significant (P < 0.01) differences in 3 instances, minimal significance (P < 0.05) of one case; and no significant difference in the remaining two cases. An investigation by t.l.c. of 41 samples from the 47 faeces with highly significant oestrogenic activity revealed dietilbestrol (Eng.: diethylstilbesterol) with concentration ranging from 17 to 666 g/kg in 24 samples; also 17 a-estradiol with concentration from 2 to 17 g/kg in 8 samples, and 17 β-estradiol, estriol and estron in lower concentration in a few samples. The results obtained clearly show the presence of synthetic hormones in female calves with "sleeping ovaries". The examination of ovaries may therefore be used to indicate whether or not oestrogen is being used illegally to fatten female beef calves.